AKIBAT HUKUM TERHADAP PEMBUATAN AKTA OTENTIK YANG TIDAK MEMENUHI KEWAJIBAN NOTARIS SEBAGAIMANA MESTINYA DIAMANATKAN DALAM UNDANG-UNDANG NOMOR 30 TAHUN 2004 TENTANG JABATAN NOTARIS (ANALISIS PUTUSAN NO.09/PDT.G/2010/PN-MBO) - SYAFRIDA YANTI (PREMISE LAW JURNAL, 2015)
The organizing of a Notary’s obligation in making authentic deed which is based on the revision of Law No. 30/2004 on Notary’s Position has been implemented although, in reality, there are still some violations against the implementation of a Notary’s obligation since there is emotional relationship between a notary and his clients, or the clients happen to be his close friends so that there is potential to be the violation against a Notary’s duty in making the minute of a deed. In this case, he sends the minute of the deed to his clients to be signed. The legal consequence of the authentic deed which is not in accordance with a Notary’s obligation, according to UUJN, related to the Ruling No. 09/Pdt.G/2010/PN-Mbo causes SKMHT No. 103/2009 is revoked for the sake of law, and it is regarded as void, and the legal consequence is that the authentic deed (Notarial Deed) becomes an underhanded deed. Here, the Notary, in making his authentic deed, has violated his own obligation in UUJN, particularly Article 16, paragraph 1, letter m of the revision of UUJN, because he is not cautious by sending the minute of the deed to his clients so that the deed  so that the deed is counterfeited by his own clients. Therefore, in this context, the Notary takes the responsibility for SKMHT No. 103/2009 because the deed contains forgery, and thus it is contrary to or against law. . Keywords: Notary, Authentic Deed, Obligation